Glutamate indicators with improved activation kinetics and localization for imaging synaptic transmission - Aggarwal, Abhi; Liu, Rui; Chen, Yang; Ralowicz, Amelia J; Bergerson, Samuel J; Tomaska, Filip; Mohar, Boaz; Hanson, Timothy L; Hasseman, Jeremy P; Reep, Daniel; Tsegaye, Getahun; Yao, Pantong; et al. (Nature methods, 2023)
The fluorescent glutamate indicator iGluSnFR enables imaging of neurotransmission with genetic and molecular specificity. However, existing iGluSnFR variants exhibit low in vivo signal-to-noise ratios, saturating activation kinetics and exclusion from postsynaptic densities. Using a multiassay screen in bacteria, soluble protein and cultured neurons, we generated variants with improved signal-to-noise ratios and kinetics. We developed surface display constructs that improve iGluSnFR's nanoscopic localization to postsynapses. The resulting indicator iGluSnFR3 exhibits rapid nonsaturating activation kinetics and reports synaptic glutamate release with decreased saturation and increased specificity versus extrasynaptic signals in cultured neurons. Simultaneous imaging and electrophysiology at individual boutons in mouse visual cortex showed that iGluSnFR3 transients report single action potentials with high specificity. In vibrissal sensory cortex layer 4, we used iGluSnFR3 to characterize distinct patterns of touch-evoked feedforward input from thalamocortical boutons and both feedforward and recurrent input onto L4 cortical neuron dendritic spines.
Keywords: Mice; neurony; Synaptic Transmission; Glutamic Acid; Kinetics; Animals; nervový přenos; synapse; Synapses; zvířata; myši; kinetika; kyselina glutamová; Neurons